Dialysis Headache: A Narrative Review. Issue 1 (28th June 2016) - Sousa Melo, Eduardo; Carrilho Aguiar, Filipe; Sampaio Rocha‐Filho, Pedro Augusto
Abstract : Background: Patients with chronic kidney disease who need dialysis often have poor quality of life. Dialysis headache is a frequent complication of hemodialysis and is often a challenge for nephrologists, neurologists, and headache specialists. Method: This was a narrative review. Results: The prevalence of dialysis headache varies between 27% and 73%. Among the characteristics of this headache are the pulsatile pattern, frontal location, moderate to severe intensity, and onset a few hours after the beginning of dialysis. The headache may be accompanied by nausea and vomiting. The physiopathology of hemodialysis headache is still not completely understood. Some factors that seem to be associated with it are variations in urea, sodium, magnesium, blood pressure, and weight levels. The hematoencephalic barrier has an important role. Variations in electrolyte and urea levels occur in the systemic circulation during hemodialysis, but the cerebral concentrations of these substances are stable over the first few hours of the procedure. The flow of free water through the hematoencephalic barrier may lead to cerebral edema. Other potential pathophysiological factors include nitric oxide, calcitonin gene‐related peptide, and substance P. There are recommendations for maintenance of volume and control over electrolytes and blood pressure and avoidance of caffeine for prevention of hemodialysis headache. However, there are no controlled studies of prophylactic or abortive hemodialysis headache treatment. Conclusion: Despite its prevalence, hemodialysis headache has been poorly studied, thus making it difficult to understand the pathophysiological mechanisms involved in its genesis. Current clinical management practices are therefore necessarily empiric with minimal to no evidence base.